Investigating the effect of emetic compounds on chemotaxis in Dictyostelium identifies a non-sentient model for bitter and hot tastant research. - Steven Robery; Janina Mukanowa; Nathalie Percie du Sert; Paul L R Andrews; Robin S B Williams (PLoS ONE)
Novel chemical entities (NCEs) may be investigated for emetic liability in a range of unpleasant experiments involving retching, vomiting or conditioned taste aversion/food avoidance in sentient animals. We have used a range of compounds with known emetic /aversive properties to examine the possibility of using the social amoeba, Dictyostelium discoideum, for research into identifying and understanding emetic liability, and hence reduce adverse animal experimentation in this area. Twenty eight emetic or taste aversive compounds were employed to investigate the acute (10 min) effect of compounds on Dictyostelium cell behaviour (shape, speed and direction of movement) in a shallow chemotaxic gradient (Dunn chamber). Compound concentrations were chosen based on those previously reported to be emetic or aversive in in vivo studies and results were recorded and quantified by automated image analysis. Dictyostelium cell motility was rapidly and strongly inhibited by four structurally distinct tastants (three bitter tasting compounds--denatonium benzoate, quinine hydrochloride, phenylthiourea, and the pungent constituent of chilli peppers--capsaicin). In addition, stomach irritants (copper chloride and copper sulphate), and a phosphodiesterase IV inhibitor also rapidly blocked movement. A concentration-dependant relationship was established for five of these compounds, showing potency of inhibition as capsaicin (IC(50) = 11.9 ± 4.0 µM) > quinine hydrochloride (IC(50) = 44.3 ± 6.8 µM) > denatonium benzoate (IC(50) = 129 ± 4 µM) > phenylthiourea (IC(50) = 366 ± 5 µM) > copper sulphate (IC(50) = 1433 ± 3 µM). In contrast, 21 compounds within the cytotoxic and receptor agonist/antagonist classes did not affect cell behaviour. Further analysis of bitter and pungent compounds showed that the effect on cell behaviour was reversible and not cytotoxic, suggesting an uncharacterised molecular mechanism of action for these compounds. These results therefore demonstrate that Dictyostelium has potential as a non-sentient model in the analysis of the molecular effects of tastants, although it has limited utility in identification of emetic agents in general.